Churches of Minnesota : an illustrated guide - Lathrop, Alan K., 1940- (University of Minnesota Press, 2003)
Photography by Bob FirthAlan Lathrop profiles more than one hundred religious buildings in a compendium made even richer by the photography of Bob Firth. More than 140 black-and-white and full-color images reveal the intrinsic character of these buildings and Lathrop uncovers the enchanting stories behind the lives of those connected to each churchthe architects, the leaders, the parishionersand the history that brought them to where they are today.